2012
DOI: 10.1097/dcr.0b013e318249d26c
|View full text |Cite
|
Sign up to set email alerts
|

A Diagnostic Accuracy Meta-analysis of Endoanal Ultrasound and MRI for Perianal Fistula Assessment

Abstract: From the available literature, the summarized performance characteristics for MRI and endoanal ultrasound demonstrate comparable sensitivities at detecting perianal fistulas, although the specificity for MRI was higher than that for endoanal ultrasound. Both specificity values are considered to be diagnostically poor, however. The high degree of data heterogeneity and the shortage of applicable studies precludes any firm conclusions being made for clinical practice. Future trials with improved study design (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
1
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 188 publications
(122 citation statements)
references
References 44 publications
1
100
1
11
Order By: Relevance
“…We did not look at sensitivity or specificity in diagnosis of fistula-in-ano. A recent metaanalysis looking into this from 2012 found the degree of heterogeneity between studies to be high, with sensitivities being reported as between 0.63 to 0.93, while the figures for specificity were 0.51 to 0.82 [24] . The numbers of sequences that could be employed are many, with several that were not assessed by us.…”
Section: A B a Bmentioning
confidence: 99%
“…We did not look at sensitivity or specificity in diagnosis of fistula-in-ano. A recent metaanalysis looking into this from 2012 found the degree of heterogeneity between studies to be high, with sensitivities being reported as between 0.63 to 0.93, while the figures for specificity were 0.51 to 0.82 [24] . The numbers of sequences that could be employed are many, with several that were not assessed by us.…”
Section: A B a Bmentioning
confidence: 99%
“…La principal indicación de la endosonografía fue incontinencia fecal, con una mayoría de población femenina, lo cual está en relación con la literatura mundial (12)(13)(14)(15)(16); también es congruente que en las mujeres con indicación del estudio por incontinencia predominó la historia de desgarro obstétrico. En su estudio descriptivo, López-Kôstner y colaboradores (4) obtuvieron como principal indicación de endosonografía anorrectal, la incontinencia fecal, presentándose en 336 pacientes de 1000 (33,6%); muy en relación con nuestro reporte, donde fue de 44%.…”
Section: Discussionunclassified
“…Several imaging modalities, as the Endoanal Ultrasound, fistulography, CT and MRI, allow the visualization of perianal fistulas [6][7][8][21][22][23][24][25][26][27][28][29]. Among these, endoanal ultrasound provides a good visualization of the intersphincteric plane and the perianal and perirectal soft tissue and is used in the assessment of patients with suspected perianal sepsis, but cannot distinguish areas of fibrosis from the active areas of inflammation and is inadequate for evaluation of ischioanal fossa and supraelevator region [21,24].…”
Section: Discussionmentioning
confidence: 99%